Perancangan Pengarsipan Berkas Permohonan Ketetapan Rencana Kota Pada UP PMPTSP Berbasis Web Menggunakan Metode Rapid Application Development (RAD) (Studi Kasus: Walikota Administrasi Jakarta Selatan) - Farrell Ezra Rasyidin (JUPIK : Jurnal Penelitian Ilmu komputer, 2023)
One of them is the ease of using technology, namely the archiving process can be used digitally. The South Jakarta Administrative Mayor Office is an office that operates for administrative affairs, especially in South Jakarta. All licensing and non-licensing documents at the South Jakarta Administrative Mayor's Office are collected in the form of archives. This manual process is feared to occur human error during the archiving process. the author proposes to create a file filing system, with the hope that with a computer system, UP PMPTSP will easily store files and files in large numbers in electronic form. Application development uses the Rapid Application Development (RAD) method. The result is that the system built can speed up the search process for important documents and on time.